Information Communication and Education Strategy of Muhammadiyah Covid-19 DKI Jakarta Province Toward Behavioral Change - Rizqiyani Khoiriyah; Sarah Handayani; Rustika Herman (Universitas Airlangga, 2022)
Background: Muhammadiyah members are the information communication and education (ICE) strategy segments from Muhammadiyah COVID-19 Command Center (MCCC). MCCC aims to deliver education and campaign programs to control COVID-19 specialized for the Muhammadiyah members. Objective: This research aims to determine social marketing strategies through the effectiveness of the MCCC website in changing Muhammadiyah members' behavior in Jakarta Province. Methods: This research was quasi-experimental with a non-randomized control group design. The sampling technique was accidental sampling, with 50 people in the intervention group and 50 in the control group. For one week, the intervention was to provide COVID-19 prevention material in PDFs, videos, and links sourced from the MCCC website. Results: The results show a significant difference in scores of behavior before and after website media intervention (p-value = 0.015). There was no significant difference before and after (p-value = 0.331). Conclusion: The intervention of media sourced from the MCCC website was able to impact the adaptation of Muhammadiyah members DKI Jakarta.